Development of Spraying Based Liquid Phase Microextraction Method for the Preconcentration of Flibanserin From Urine Samples via GC-MS Analyses - Kasa, Nursu Aylin; Bodur, Suleyman; Zaman, Buse Tugba; Bakirdere, Sezgin (WILEY, 2026)
Flibanserin is the initial pharmaceutical treatment for hypoactive sexual desire disorder (HSDD). The analysis of urine samples plays a crucial role in the quantitation of flibanserin since a portion of flibanserin is excreted unchanged in the urine. An analytical method was proposed to quantify flibanserin in artificial urine samples (as model matrices). The integration of the spray-assisted fine droplet formation-liquid phase microextraction (SFDF-LPME) method and gas chromatography-mass spectrometry (GC-MS) system was performed for the first time to improve the sensitivity of the GC-MS system for flibanserin. Several parameters, including spraying cycle, extraction solvent type, mixing type and period, and sample volume, were systematically optimized to enhance the signal-to-noise ratio (S/N) of the analyte. After determining the optimal conditions, the analytical performance measurements of the system were figured out. The limit of detection (LOD), the limit of quantification (LOQ), and coefficient of determination (R-2) values were 6.91, 23.05 mu g kg(-1), and 0.9989, respectively. Recovery experiments were performed in artificial urine samples within the specified linear working range of 33.15-505.66 mu g kg(-1). The SFDF-LPME-GC-MS method was efficiently applied to artificial urine samples by computing the matrix-matching calibration strategy, with percentage recovery values ranging from 90.0% to 105.9%.
Keywords: artificial urine samples; flibanserin; gas chromatography-mass spectrometry; spray assisted fine droplet formation-liquid phase microextraction; PERFORMANCE; Biochemistry & Molecular Biology; Chemistry; Pharmacology & Pharmacy